2022
DOI: 10.3390/ijms23158555
|View full text |Cite
|
Sign up to set email alerts
|

Combining Physio-Biochemical Characterization and Transcriptome Analysis Reveal the Responses to Varying Degrees of Drought Stress in Brassica napus L.

Abstract: Brassica napus L. has become one of the most important oil-bearing crops, and drought stress severely influences its yield and quality. By combining physio-biochemical characterization and transcriptome analysis, we studied the response of B. napus plants to different degrees of drought stress. Some physio-biochemical traits, such as fresh weight (FW), dry weight (DW), abscisic acid (ABA) content, net photosynthetic rate (Pn), stomatal conductance (gs), and transpiration rate (Tr), were measured, and the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Rapeseed is one of the most important seed oil‐bearing crops, but drought stress severely influences its growth and yield (Fang et al, 2022). Drought stress can induce ABA and proline accumulation (Cheng et al, 2022; Ren et al, 2018), and thereby induce a series of responses, such as stomatal movement (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Rapeseed is one of the most important seed oil‐bearing crops, but drought stress severely influences its growth and yield (Fang et al, 2022). Drought stress can induce ABA and proline accumulation (Cheng et al, 2022; Ren et al, 2018), and thereby induce a series of responses, such as stomatal movement (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis of another representative of Brassicaceae-rapeseed (Brassica napus) revealed that most significantly enriched GO terms of the upregulated DEGs were related with the response to water deprivation, ABA signaling, osmotic stress, and other abiotic stimuli and lipid metabolism as well as cutin, suberin, and wax biogenesis, fatty acid degradation and secondary compound metabolism. On the contrary, downregulated DEGs were connected mainly with photosynthetic activities, porphyrin metabolism, carbon, and nitrogen metabolism [110].…”
Section: Water Deficiency (Drought)mentioning
confidence: 94%
“…There were 795 genes up‐regulated and 1,050 genes down‐regulated under severe drought stress. Among them, overexpression of calcineurin B‐like protein (CBL)‐interacting protein kinase ( BnA01.CIPK6 ) was found to improve drought tolerance (Fang et al, 2022). With the rise of phenomics, drought‐related phenotypes can be accessed more precisely in the future to aid in the identification of drought resistance genes in B. napus .…”
Section: Abiotic Stressmentioning
confidence: 99%